If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
7-((3*x)/4) = 34 // - 34
7-((3*x)/4)-34 = 0
(-3/4)*x-34+7 = 0
-3/4*x-27 = 0 // + 27
-3/4*x = 27 // : -3/4
x = 27/(-3/4)
x = -36
x = -36
| 2x-2=22-4x | | 8x^2-23x-36=0 | | ln(a-10)-1=0 | | 5x+10-x=10 | | 7-3x=6x-56 | | 4(4x+1)=4x-7x | | 13/3x-2=4/x | | x^4+5*x^3+9*x^2+8*x+4=0 | | 3-7x+2x=-37 | | 9x-26=30-5x | | 12t^2-5t+6=8 | | ln(p+10)=1 | | 8w+8=16 | | -9y+9=72 | | 0.30x+0.20(60)=0.15(32) | | -5(2x-9)=2(x-6)-11 | | 4x^4+8x^3+16x^2=0 | | 13x+3=29 | | 4w/3=4 | | 96x-624=336 | | -x+4x=8x-x+6 | | ln(6n)=3 | | (3x+3y)2= | | 5-2y=2+4y | | -5+x=-6x-5 | | f(x)=5-x^2/4 | | 0.36-a^2=0 | | 15=3r-3 | | 0.2047244=(1800*(96^3))/((10*10^6)*48*((b*(3.75^3)-(b-.5)*(3.25^3))/12)) | | 5.3x-6.45=7.95-4.3z | | g(-3)=0 | | -6x-3=5/7x-538/7 |